Investigating the Relationship between Leukocyte Activities and Inflammatory Markers in Obese Adults - Al-khafaji, Teeb M. Jaafar (American Journal of Biology and Natural Sciences, 2025)
This study is designed to evaluate the relationship between the activities of leukocytes and some inflammatory markers in obese adults. Leukocytes, as pivotal actors in inflammation states, play a vital role in chronic low-grade inflammation, a characteristic sign of obesity. In these experiments, we investigated the relationship of immune response parameters, namely total leukocyte counts and differentiation, to important obesity mediators, namely, C-reactive protein (CRP), interleukin-6 (IL-6) and Tumor necrosis factor-alpha (TNF-alpha). Specifically, 100 obese subjects were enrolled. The results of the experiments are encouraging. Robust and significant correlations are seen between total leukocytes, neutrophils, monocytes and important inflammatory markers. This means that we have identified leukocyte parameters that can be used to detect and follow obesity-related inflammation. This is good news, and means that our research results are likely to be valid.